Engineered Proteinticles for Targeted Delivery of siRNA to Cancer Cells - Lee, Eun Jung; Lee, So Jin; Kang, Yoon-Sik; Ryu, Ju Hee; Kwon, Koo Chul; Jo, Eunji; Yhee, Ji Young; Kwon, Ick Chan; Kim, Kwangmeyung; Lee, Jeewon (WILEY-V C H VERLAG GMBH, 2015)
Considering the problems of small interfering RNA (siRNA) delivery using traditional viral and nonviral vehicles, a new siRNA delivery system to enhance efficiency and safety needs to be developed. Here human ferritin-based proteinticles are genetically engineered to simultaneously display various functional peptides on the surface of proteinticles: cationic peptide to capture siRNA, tumor cell targeting and penetrating peptides, and enzymatically cleaved peptide to release siRNA inside tumor cell. In the in vitro treatment of poly-siRNA-proteinticle complex, both of the tumor cell targeting and penetrating peptides are important for efficient delivery of siRNA, and the red fluorescent protein (RFP) expression in RFP-expressing tumor cells is notably suppressed by the delivered siRNA with the complementary sequence to RFP mRNA. It seems that the human ferritin-based proteinticle is an efficient, stable, and safe tool for siRNA delivery, having a great potential for application to in vivo cancer treatment. The unique feature of proteinticles is that multiple and functional peptides can be simultaneously and evenly placed and also easily switched on the proteinticle surface through a simple genetic modification, which is likely to make proteinticles appropriate for targeted delivery of siRNA to a wide range of cancer cells.